Beyond boundaries: Charting the frontier of healthcare with big data and ai advancements in pharmacovigilance - Arohi Agarwal; Gagan Singh; Samyak Jain; Piyush Mittal (Health Sciences Review)
The healthcare sector is intricate, generating vast amounts of data from various sources at an accelerated pace. The contemporary trend of Big Data Analytics is pivotal, impacting not only the pharmaceutical industry but also transforming healthcare, contributing to personalized treatment, aiding in preventive healthcare, managing electronic health records, facilitating adverse drug reporting, and incorporating consumer reviews. This article provides an overview of the inevitable influence of big data and the utilization of artificial intelligence in revolutionizing both healthcare and the pharmaceutical sector. It delves into the notable benefits and challenges encountered in advancing data analytics of the early 21st century.In many countries, Post-marketing surveillance of drug safety relinquishes on a systematic analysis of spontaneous using Generative artificial intelligence (AI) to overcome gaps in the present PV ecosystem is critical to maintaining an uninterrupted record of security and effectiveness within healthcare analytics, data mining techniques, predictive analytics, and the emergence of scientific fields like bioinformatics and health informatics are empowered by Big Data. Nevertheless, the integration of AI in healthcare, especially in pharmacovigilance, aligns with the evolving landscape of electronic health information technology. In conclusion, review highlights the transformative impact of Big Data and AI in healthcare, emphasizing their applications in pharmacovigilance and pharmacoepidemiology. The continuous evolution of these technologies holds promise for improving patient safety, personalized medicine, and overall healthcare outcomes.